2017
DOI: 10.15294/jbat.v6i2.9621
|View full text |Cite
|
Sign up to set email alerts
|

CHARACTERISTICS OF DEMINERALIZED GELATIN FROM LIZARDFISH (Saurida spp.) <br> SCALES USING NaOH-NaCl SOLUTION

Abstract: Demineralization is required to reduce the ash content of gelatin. Previous studies have confirmed the high quality of gelatin was produced after demineralized using combination of NaCl and aqueous NaOH. The purpose of this study was to determine the effect of NaCl on the properties of gelatin from Lizardfish (Saurida spp.) scales. The cleaned scales was demineralized using a mixture of NaOH 0.5% and NaCl (0-0.8%), at various temperatures (45, 65, 86oC) and time (30, 60, 90 and 150 minutes). The obtained sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
1
1
0
7
Order By: Relevance
“…The decrease in ash content indicates the absence of inorganic salt content in the gelatin produced during pre-treatment with acid (Ahmad and Benjakul, 2011). In line with that, Wardhani et al (2017) also reported that the ash content was affected by the demineralisation process during gelatin extraction from fish scales, and this content process was reduced by using NaCl and NaOH. The fat content of rabbit bone gelatin in this current study ranged from 0.03 to 0.1%, which was much lower than that stipulated by Standar Nasional Indonesia (SNI) 06-3735-1995, which is a maximum of 5%.…”
Section: Resultssupporting
confidence: 72%
“…The decrease in ash content indicates the absence of inorganic salt content in the gelatin produced during pre-treatment with acid (Ahmad and Benjakul, 2011). In line with that, Wardhani et al (2017) also reported that the ash content was affected by the demineralisation process during gelatin extraction from fish scales, and this content process was reduced by using NaCl and NaOH. The fat content of rabbit bone gelatin in this current study ranged from 0.03 to 0.1%, which was much lower than that stipulated by Standar Nasional Indonesia (SNI) 06-3735-1995, which is a maximum of 5%.…”
Section: Resultssupporting
confidence: 72%
“…Pengujian pH gelatin tulang ikan bandeng mengacu pada cara yang dilakukan oleh Wardhani et al (2017). Sampel sebanyak 0,2 gram dilarutkan ke dalam air dengan suhu 25 o C kemudian dihomogenkan menggunakan magnetic stirrer.…”
Section: Metode Pengujian Ph Gelatinunclassified
“…Pengujian viksositas gelatin tulang ikan bandeng mengacu pada cara yang dilakukan oleh Wardhani et al (2017). Sampel dilarutkan dalam air dengan suhu 60 o C hingga mencapai konsentrasi 6,67% (b/v).…”
Section: Merode Pengujian Viskositas Gelatinunclassified
“…Sebanyak 50 -70% bobot ikan adalah sisik dan tulang ikan. 10,11 Indonesia memiliki hasil perikanan yang melimpah, namun pemanfaatan limbah tulang ikan belum optimal. Tulang ikan berpotensi digunakan untuk menghasilkan gelatin yang dapat digunakan dalam pembuatan cangkang kapsul.…”
Section: Hasil Dan Pembahasanunclassified